2019
DOI: 10.1590/1983-40632019v4954201
|View full text |Cite
|
Sign up to set email alerts
|

Silicon accumulation and its effect on agricultural traits and anthracnose incidence in lignocellulosic sorghum

Abstract: Silicon (Si) accumulation in plants may reduce yield losses by inducing resistance to both abiotic and biotic stresses. This study aimed to evaluate the Si accumulation by lignocellulosic sorghum (Sorghum bicolor) in a greenhouse experiment, as well as the effect of its application on agricultural traits and on the induction of resistance against anthracnose (Colletotrichum sublineolum) in a field experiment. Sixteen sorghum genotypes were evaluated in a greenhouse for their response to silicate fertilization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
5
0
2
Order By: Relevance
“…The variation could also be influenced by the experimental factors. However, previous studies showed that there can be a genotype influence in the capability of sorghum plants to absorb Si (de Lima et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…The variation could also be influenced by the experimental factors. However, previous studies showed that there can be a genotype influence in the capability of sorghum plants to absorb Si (de Lima et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…However, Si favored the photochemical stability of E. myrcianthes seedlings by increasing the synthesis of chlorophylls (Figure 2), especially at the stress phase. This element contributes to the plant architecture, leaving the leaves more erect and rigid (Tubana et al, 2016;Lima et al, 2019), favoring solar interception and reflecting a higher production of photoassimilates, increment in leaves, and photosynthetic area (leaf area) and biomass production (DMT), a result different from that of seedlings not treated with Si.…”
Section: Discussionmentioning
confidence: 99%
“…In the plant, Si provides higher structural rigidity of the tissue, favors osmotic adjustment (Yin et al, 2013;Lima et al, 2019), and increases photosynthetic and water use efficiency (Cooke and Leishman, 2016;Thorne et al, 2020;Cassol et al, 2021), regulating physiological processes. The beneficial effect of Si is associated with the fact that this element promotes an increase in photosynthetic pigments and gene and phytohormone expressions, in addition to the activity of antioxidant enzymes and amino acids capable of relieving or delaying oxidative stress (Chen et al, 2011;Parveen et al, 2019).…”
Section: Evaluated Morphophysiological Characteristicsmentioning
confidence: 99%
“…Diante da importância desse elemento, pesquisas com biofortificação agronômica de plantas têm sido amplamente realizadas nos últimos anos (SILVA et al 2013, MIRANDA et al 2018, LIMA et al 2019) e, apesar de não ser considerado essencial às plantas, a aplicação deste elemento pode propiciar vantagens às culturas.…”
Section: Introductionunclassified